1955
DOI: 10.1139/m55-045
|View full text |Cite
|
Sign up to set email alerts
|

THE ISOLATION OF MYCOBACTERIUM TUBERCULOSIS BY FILTRATION TECHNIQUE FROM CEREBROSPINAL FLUID

Abstract: Collection on a filter membrane as a routine culture method has proved of great advantage in the isolation of Mycobacterium tuberculosis from the cerebrospinal fluid. Its use, during combined intrathecal treatment with streptomycin and Purified Protein Derivative of tuberculin, shows that the organisms persist for an unexpectedly long time in the cerebrospinal fluid. In some instances, focal reaction to P.P.D. seems to liberate tubercle bacilli from the lesions into the fluid. Direct culture of C.S.F. on Loewe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1958
1958
2020
2020

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Aside from the coliforms and enterococci, growth of several other organisms has been described. Rogers et al (1955) and Morgante and Murray (1955) reported on cultivation of the tubercle organism; Orlando and Bolduan (1953) demonstrated growth of a variety of bacteria and fungi imperfecti on the MF. Gaspar and Leise (1955,1956) studied growth of Brucella melitensis and Bacterium tularense 1 This work was supported by the Office of Naval Research and the Bureau of Medicine and Surgery under ONR contract with the University of California, Berkeley, California.…”
mentioning
confidence: 99%
“…Aside from the coliforms and enterococci, growth of several other organisms has been described. Rogers et al (1955) and Morgante and Murray (1955) reported on cultivation of the tubercle organism; Orlando and Bolduan (1953) demonstrated growth of a variety of bacteria and fungi imperfecti on the MF. Gaspar and Leise (1955,1956) studied growth of Brucella melitensis and Bacterium tularense 1 This work was supported by the Office of Naval Research and the Bureau of Medicine and Surgery under ONR contract with the University of California, Berkeley, California.…”
mentioning
confidence: 99%